2017
DOI: 10.1111/jnc.14141
|View full text |Cite
|
Sign up to set email alerts
|

The aberrantly expressed long non‐coding RNA in the substantia nigra and corpus striatum of Nrf2‐knockout mice

Abstract: Nuclear factor erythroid 2 like 2 (Nrf2) functions as a neuroprotective agent in Parkinson's disease (PD). This study aimed to investigate the key long non-coding RNAs (lncRNAs) correlated with Nrf2, which might provide valuable information for the exploration of pathogenesis of PD. The lncRNA and mRNA expression profiling of substantia nigra and corpus striatum of Nrf2 (-/-) mice model was obtained from microarray analysis. The animal experiments conducted for this study were approved by the ethics committee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our previous study has identified 96 and 643 DEmRNAs in the substantia nigra and corpus striatum between Nrf2 (-/-) and Nrf2 (+/+) mice, respectively [28]. After these DEmRNAs were retained to construct the DEcircRNA-miRNA-DEmRNA interaction network, mmu_circRNA_015216, mmu_circRNA_32463, mmu_circRNA_34106 and mmu_circRNA_34132 were predicted to compete with 10, 11, 8 and 17 DEmRNAs in the substantia nigra between Nrf2 (-/-) and Nrf2 (+/+) mice, respectively; and mmu_circRNA_33836, mmu_circRNA_017077 and mmu_circRNA_003119, mmu_circRNA_34132 and mmu_circRNA_34106 were predicted to compete with 22, 80 and 18, 169 and 78 DEmRNAs, respectively, in the corpus striatum between Nrf2 (-/-) and Nrf2 (+/+) mice.…”
Section: Decircrna-mirna-demrna Interaction Networkmentioning
confidence: 99%
“…Our previous study has identified 96 and 643 DEmRNAs in the substantia nigra and corpus striatum between Nrf2 (-/-) and Nrf2 (+/+) mice, respectively [28]. After these DEmRNAs were retained to construct the DEcircRNA-miRNA-DEmRNA interaction network, mmu_circRNA_015216, mmu_circRNA_32463, mmu_circRNA_34106 and mmu_circRNA_34132 were predicted to compete with 10, 11, 8 and 17 DEmRNAs in the substantia nigra between Nrf2 (-/-) and Nrf2 (+/+) mice, respectively; and mmu_circRNA_33836, mmu_circRNA_017077 and mmu_circRNA_003119, mmu_circRNA_34132 and mmu_circRNA_34106 were predicted to compete with 22, 80 and 18, 169 and 78 DEmRNAs, respectively, in the corpus striatum between Nrf2 (-/-) and Nrf2 (+/+) mice.…”
Section: Decircrna-mirna-demrna Interaction Networkmentioning
confidence: 99%
“…Further, 279/164 upregulated lncRNAs and 477/177 downregulated lncRNAs were found in -SNCA * A30P * A53T transgenic mice and alpha-synuclein transgenic mice [53,55], respectively. In Nrf2 knockout mice, 74 upregulated lncRNAs and 160 downregulated lncRNAs were found [54]. Differential lncRNA expression in conventional nontransgenic PD models has also been studied.…”
Section: Aberrant Expression Of Lncrnas In Pdmentioning
confidence: 99%
“…In our previous study, we detected the altered expression of circRNAs and lncRNAs in the substantia nigra and corpus striatum tissue of Nrf2-null mice (Liu J. et al, 2017; Yang et al, 2018), and considering that Nrf2 activity may diverge across different brain regions, the current study focused on the expression profiles of circRNAs and lncRNAs in the hippocampus tissue of Nrf2-null mice. Previous studies showed definitively that the hippocampus and neighboring structures of the medial temporal lobe are essential to memory (Preston and Eichenbaum, 2013).…”
Section: Introductionmentioning
confidence: 99%